The Implementation of the Crossword Puzzle Learning Model to Improve Elementary School Students’ Learning Motivation in Music Arts - Andi Adelia Putri Ramadani; Awaluddin Muin; Sidrah Afriani Rahman (Journal of Primary Education Innovation and Research, 2025)
This study aims to improve students’ learning motivation in Music Arts through the implementation of the Crossword Puzzle learning model in Grade VI of SD Inpres 4/82 Pacing, Kabupaten Bone. This study used a qualitative approach with Classroom Action Research as the research design. The subjects of this study were one teacher and 12 sixth-grade students, consisting of 5 male students and 7 female students. Data were collected through observation and questionnaires, while the data were analyzed through data reduction, data presentation, and conclusion drawing. The research was conducted in two cycles, and each cycle consisted of planning, action, observation, and reflection stages. The results showed that the implementation of the Crossword Puzzle learning model improved teacher activity, student activity, and students’ learning motivation. In Cycle I, teacher activity reached 72.72% and student activity reached 69.69%, both categorized as fair. Students’ learning motivation in Cycle I showed that 7 out of 12 students reached the success indicator, with a percentage of 58.33%. In Cycle II, teacher activity and student activity increased to 96.96%, both categorized as good. Students’ learning motivation also increased, with 10 out of 12 students reaching the success indicator, or 83.33%. These findings indicate that the Crossword Puzzle learning model can create a more enjoyable, active, and interactive learning process. Therefore, the Crossword Puzzle learning model can be used as an alternative strategy to improve students’ learning motivation in Music Arts at the elementary school level.